IMPROVING THE INSTITUTION OF COURT COSTS THROUGH THE EXPERIENCE OF FOREIGN COUNTRIES - Sulaymonova Nargiza Muxiddinovna (Modern American Journals, 2026)
This article aims to examine the problems currently arising in the recovery of court costs in civil proceedings, to analyze and evaluate them, and to explore possible solutions by studying the experience of foreign countries, in particular Germany and Japan. In addition, the article identifies existing shortcomings in the legislation of the Republic of Uzbekistan and proposes relevant recommendations, including amendments and additions to legal acts aimed at improving the regulation of court costs.
Keywords: State duty, litigation-related expenses, refund of state duty, court hearing, expedited court.